Second-trimester uterine rupture: lessons learnt - Abdulwahab, Dalia F; Ismail, Hamizah; Nusee, Zalina (Universiti Sains Malaysia, 2014)
Uterine rupture is a rare life-threatening complication. It mainly occurs in the third trimester of pregnancy and is rarely seen during the first or second trimesters. Our centre experienced three important cases of uterine rupture. First case: spontaneous uterine rupture at 14 weeks of pregnancy, which was diagnosed at autopsy. It was misled by the ultrasound finding of an intrauterine pregnancy, and searching for other non-gynaecological causes delayed the urgent obstetric surgical management. Second case: ruptured uterus at 24 weeks following medical termination due to foetal anomaly. It was diagnosed only at laparotomy indicated for failed medical termination and chorioamnionitis. Third case: uterine rupture at 21 weeks of pregnancy in a patient with gastroenterology symptoms. In these reports, we have discussed the various risk factors, presentations, course of events and difficulties in diagnosing uterine rupture. The study concludes that the clinical presentation of uterine ruptures varies. It occurs regardless of gestational age. Ultrasound findings of intrauterine pregnancy with free fluid do not exclude uterine rupture or ectopic pregnancy. Searching for non-gynaecological causes in such clinical presentations might delay crucial surgical intervention, which leads to unnecessary morbidity, mortality or loss of obstetrics function.